ANALISIS NILAI TAMBAH BUAH PISANG MENJADI KERIPIK PISANG PADA INDUSTRI RUMAH TANGGA DI DESA DIMEMBE KECAMATAN DIMEMBE - Vinny ., Makarawung; Paulus A. Pangemanan; Caroline B. D. Pakasi (Sam Ratulangi University, 2017)
The purpose of this study is to calculate the profit and added value of the business of processing bananas into banana chips. This research is carried out for two months, from April to May 2017. The research place in one household industry of banana chips in Dimembe Village, Dimembe Sub-district, North Minahasa Regency. The method used in this research is by taking primary data and secondary data. Primary data was obtained through direct interviews using questionnaires. Secondary data is obtained through literature that supports and is associated with this research. Data analysis methods used in this study are: (1) calculate the Benefits of Banana Processing Business Being Chips, (2) calculate the Value Added Banana Chips. The results of this study indicated that the Agro-Business Processing of Banana Chips provides a benefit received is IDR 5,313,500 per month or twenty-three times of the production process. The value added enjoyed by the owner of agroindustry amounted to Rp 2.404/kg from raw materials used. This added value is an advantage gained by banana chips agroindustry in 1 kilogram of raw material usage.